Virtual reality in heritage education for enhanced learning experience: a mini-review and design considerations - Zhao, Yiqing; Li, Yaning; Dai, Tianchen; Sedini, Carla; Wu, Xue; Jiang, Weile; Li, Ji; Zhu, Kaiyi; Zhai, Binqing; Li, Meng; LC, RAY (Frontiers in Virtual Reality, 2025)
Heritage education is a key approach to preserving and transmitting a community’s history and culture embedded in its collective memory, fostering social cohesion, and cultivating a sense of identity among different populations. Bridging the gap between historical narratives and contemporary audiences is central to promoting educational outcomes. In recent years, rapid advances in digital technologies have provided unprecedented opportunities for the preservation, inheritance, and dissemination of cultural heritage. Virtual reality (VR), with its ability to create three-dimensional representations of real or imagined locations, provides a compelling sense of realism, illustrating its potential for various applications in cultural heritage preservation, such as 3D historical reconstruction, enhanced tourism engagement, gamified learning, and pedagogical cultural heritage programs. This mini-review focuses on VR-enhanced heritage education, a field that involves transdisciplinary studies on the dynamics of user engagement and virtual experiences tailored for cultural heritage education. The aim of this mini-review is to investigate the current status, identify limitations, and outline prospective design considerations for integrating VR technology into heritage education. In this study, we will provide insights into future design considerations for designers, developers, and educators in order to create better heritage education experiences, contributing to developing interactive approaches to heritage education.